LIVE LABORATORY: THE THEATER EXPERIENCE IN A GROUP, FAN AL-HAYAT WORKSHOP [THE ART OF LIFE] - Samir Reyad-Mamdoh (Cena, 2021)
This research proposes to study a theatrical experience conducted in a group to explore the potential of theatrical work. A working protocol was established: training to work on dynamic positions, contact and body plasticity, and preparation for the theatrical game, conducted with the aim of establishing the distance between the actors and the events that affect them, in order to overcome them. Theatrical action was a source of discovery, of working on oneself, an effective means of helping them to be free, sharing their feelings, controlling their fragility, recovering an ability to act until then ignored. They rebuilt themselves, finding self-confidence and re-appropriating other skills and attitudes. It is a path that can lead to resilience. Our empirical study combines two intrinsic dimensions: theory, allowing us to think about our approach and include it in a reflective process; and the practice that offers us the possibility to carry out an experience of working on the stage, in the exploration of personal goals and inhibitions.